ISSUES RELATED TO THE CURRENT STATE OF TRANSPORT INFRASTRUCTURE - Bahrii, Mariia; Konovalova, Elena; Chaika , Natalia; Razumova, Kateryna (Science-based technologies, 2021)
The article presents the analysis of state-of-the-art problems of transport infrastructure of Ukraine as part of the world transport system. Using statistical data presented on the web-site of the State Statistics Service f Ukraine and data provided by airport operators passenger and cargo traffic were studied taking into account limitations due to quarantine requirements during 2020 and January-May 2021. The analysis of statistical data shows that traffic grows: passenger traffic grows up to 8,2% and cargo traffic – up to 1,5% by mode of transport. Priority infrastructure projects for realization of the «National transport strategy 2030» (hereinafter – the «Strategy-2030») were reviewed. Analysis of the principals of the «Strategy» shows that transport infrastructure of Ukraine has low level of implementation of transport-logistic technologies and objects of multimodal transport, which reduces its competitiveness and enables them to rejoin the global transport markets. The analysis of the «Strategy-2030» showed principal directions of transport infrastructure of Ukraine. Implementation of latest advanced technologies and techniques, which provide operation and information support for passenger and cargo traffic, is substantiated. As a focus target the need for creation an integrated informational network and interaction of all transport modes of Ukraine is stated. It should be noted that realization of the «Strategy-2030» aims at improving of safety, security, quality and accessibility of transport